ANALYSIS EKONOMIKO-LEGAL STATUS OF CITY IN UKRAINE - Родченко, В. Б.; Серѐгина, Д. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
Within the framework of this work the comprehensive analysis of concept «city» was conducted in a legal and economic context, and also factors, influencing on subsuming of settlement cities in Ukraine and world.